EKSPERIMEN PERBANDINGAN OLAHAN KULIT PISANG RAJA DAN CHICKPEA DALAM PEMBUATAN PATTY SEBAGAI ALTERNATIF VEGETARIAN - Hendra Syaiful; Agung Arif Gunawan; Silitonga, Frangky (JURNAL MANAJEMEN KULINER, 2022)
The vegetarian diet has become a dietary pattern that many people have started to choose along with increasing public knowledge of the benefits of a plant-based diet to reduce the risk of diseases that can harm the body.. One of the vegetable ingredients used in this study were banana peels and chickpeas as a comparison. Banana peels and chickpeas have good nutritional content and can be processed into a variety of food products. Besides being used as food raw material, it also improves nutritional content when processed into food. So that this effort can be done in making a vegetarian patty made from vegetable, namely banana peel as an alternative for vegetarians. This research is an experimental study of making a vegetarian patty with plantain peels and chickpeas as an alternative for vegetarians. Data collection techniques used instruments in the form of hedonic quality test and hedonic test with data analysis used, namely the Mann-Whitney test to determine the difference between 2 treatments or treatments. The research instrument used a questionnaire with a total of 20 panelists trained. The results of the hedonic quality test showed that there was no difference in texture, aroma and color in the Vegetarian Patty made from banana peels and Chickpea nut. However, there are differences in the taste of the Vegetarian Patty processed by banana peels and chicpea nut. The hedonic test results, the panelists liked the taste, aroma, and texture of the Vegetarian Patty made with Chickpea nut while for the color, the panelists liked the color of the Vegetarian Patty with the processed banana peels.